The Study of the Synthesis of SiC by the Carbonization of Si(111) Substrates: The Role of Native Silicon Oxide - Teodor Milenov; Vladimir Mehandzhiev; Peter Rafailov; Ivalina Avramova; Ivan Zahariev; Georgi Avdeev; Daniela Karashanova; Biliana Georgieva; Penka Terziyska; Kiril Kirilov; Blagoy Blagoev; Stefan Kolev; et al. (Applied Sciences, 2025)
We present the results of silicon carbide (SiC) thin film synthesis on Si(111) substrates using chemical vapor deposition by decomposing CH4 in H2 at 1135 °C. The experiments were conducted in an Oxford Nanofab Plasmalab System 100 for carbon phase deposition times of 3, 5, 20, 60, and 90 min on Si(111) with or without native oxide, following established protocols. Our studies show that either predominantly crystalline SiC or a mixture of SiC and Si–O/Si–O–C glass forms on Si substrates significantly doped with carbon and oxygen, depending on the presence or absence of native oxide. The thickness of the SiC film ranges from approximately 5–6 nm for films synthesized in 3 min to over 15 nm for those synthesized in 90 min, while the size of the crystal grains varies from a few to 110 nm depending on the synthesis duration. The findings suggest that the complex composition of the thin films and the region beneath them can more effectively compensate for the differences in lattice parameters and thermal expansion coefficients between the SiC film and the Si substrate; thus, this method is promising for depositing intermediate thin films of SiC on Si substrates.